Synthesis of 1D upconversion CeO2:Er, Yb nanofibers via electrospinning and their performance in dye-sensitized solar cells. Issue 54 (13th June 2015) - Bai, Jingyi; Zhao, Rongfang; Han, Gui; Li, Zhongcui; Diao, Guowang
<x xml:space="preserve">Abstract</x> 1D upconversion CeO2:Er, Yb nanofibers, which absorb NIR light and upconvert it to visible light to increase the photocurrent of DSSCs, have been fabricated by an electrospinning method. An enhancement of 14% in the light harvesting efficiency was observed.